THE IMPACT OF EARNING PER SHARE, RETURN ON ASSET AND FIRM SIZE TOWARD INITIAL RETURN OF MANUFACTURING COMPANIES CONDUCTING INITIAL PUBLIC OFFERING LISTED IN INDONESIA STOCK - Shelly Kevin; Yenni Martok (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
The rapid development of the era will have an impact on several parts of life, including business. Intense competition in business requires expansion and innovation for companies to survive. The corporation will need a huge amount of money to execute it. Going public and executing an IPO, which is an initial public offering of shares made by the company, is one source of funding. The IPO share price is decided by an agreement between the Company and the Underwriter. There were two phenomena that could happen at the time of the IPO, namely underpricing and overpricing which both occurred due to price differences in the primary and secondary markets. The purpose of this study is to analyse the effect of Earning per Share, Return on Assets and Firm Size on Initial Return. This study focuses on manufacturing companies that carry out IPOs listed on the Indonesia Stock Exchange from 2018-2020. This study employs a multiple linear analysis model, with 32 companies serving as the sample. The result of the study partially indicates that Earning per Share does not impact Initial Return. Return on Assets has a positive and insignificant impact on Initial Return. Furthermore, Firm size has a negative and significant impact on Initial Return. But simultaneously, Earning per Share, Return on Assets, and Firm Size have no impact on Initial Return.BAHASA INDONESIA ABSTRACTPerkembangan zaman yang pesat akan mempengaruhi banyak aspek kehidupan dan salah satunya yakni bisnis. Persaingan yang ketat dalam bisnis, membutuhkan ekspansi dan inovasi bagi perusahaan untuk dapat bertahan. Untuk melakukan hal tersebut, perusahaan memerlukan dana cukup besar. Salah satu sumber pendanaan yaitu go public atau Initial Public Offering (IPO) yang dimana merupakan penawaran umum penjualan perdana saham yang dilakukan oleh perusahaan. Harga saham pada saat IPO ditentukan oleh persetujuan antara Perusahaan dan Penjamin Emisi (Underwriter). Terdapat dua fenomena pada saat IPO yakni underpricing dan overpricing yang dimana fenomena ini terjadi karena perbedaan harga saham pada pasar primer dan pasar sekunder.Penelitian ini bertujuan untuk menganalisis pengaruh dari Earning per Share, Return on Asset, dan Firm Size terhadap Initial Return. Penelitian ini memfokuskan pada perusahaan manufaktur yang melakukan IPO dan terdaftar pada Bursa Efek Indonesia dari tahun 2018-2020. Penelitian ini menggunakan model analisis linear berganda dengan total 32 perusahaan sebagai sampel pengujian. Hasil penelitian secara parsial menunjukkan bahwa Earning per Share tidak berdampak pada Initial Return. Return On Asset berdampak positif dan tidak signifikan terhadap Initial Return. Dan Firm size berdampak negatif dan signifikan terhadap Initial Return. Namun secara simultan, Earning Per Share, Return On Asset, dan Firm Size tidak berdampak terhadap Initial Return.